2014
DOI: 10.1002/ange.201310116
|View full text |Cite
|
Sign up to set email alerts
|

Magnesiacyclopentadienes as Alkaline‐Earth Metallacyclopentadienes: Facile Synthesis, Structural Characterization, and Synthetic Application

Junnian Wei,
Liang Liu,
Ming Zhan
et al.

Abstract: Metallacyclopentadienes have attracted much attention as building blocks for synthetic chemistry as well as key intermediates in many metal-mediated or metal-catalyzed reactions. However, metallacyclopentadienes of the alkalineearth metals have not been reported, to say nothing of their structures, reaction chemistry, and synthetic applications. In this work, the first series of magnesiacyclopentadienes, spirodilithio magnesiacyclopentadienes, and dimagnesiabutadiene were synthesized from 1,4-dilithio 1,3-buta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…We recently reported afacile synthesis of multisubstituted magnesiacyclopentadienes (1)asthe first example of alkalineearth metallocyclopentadienes. [4] Single-crystal X-ray structural analysis of these magnesiacyclopentadienes revealed an early coplanar ring skeleton. Although the lengths of the chemical bonds of the ring, including two Mg À C(sp 2 )b onds, are comparable to those reported, the bite angle of C1-Mg-C4 (91.548 8)ismuch smaller than the classic C-Mg-C angles in the usual tetracoordinate magnesium compounds (115-1308 8).…”
Section: Organocopper(i) Compounds Are Ubiquitously Involved Inmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported afacile synthesis of multisubstituted magnesiacyclopentadienes (1)asthe first example of alkalineearth metallocyclopentadienes. [4] Single-crystal X-ray structural analysis of these magnesiacyclopentadienes revealed an early coplanar ring skeleton. Although the lengths of the chemical bonds of the ring, including two Mg À C(sp 2 )b onds, are comparable to those reported, the bite angle of C1-Mg-C4 (91.548 8)ismuch smaller than the classic C-Mg-C angles in the usual tetracoordinate magnesium compounds (115-1308 8).…”
Section: Organocopper(i) Compounds Are Ubiquitously Involved Inmentioning
confidence: 99%
“…TheM ga toms are tetracoordinated by two alkenyl carbon atoms,one bromide atom, and one oxygen atom. Compared to that in the magnesiacyclopentadiene 1a-TMEDA, [4] However,the C-Cu-C bond angle [156.8(4)8 8]issignificantly less obtuse than that of diaryl lithium organocuprates (163-1788 8), which indicates that ahigher degree of covalencyinthe Mg À Cbond induces ac orresponding increase in the CuÀCÀMg three-center-twoelectron bonding character. [3f] TheC u ÀMg distance [2.709-(2) ]i ss horter than the sum of van der Waals radii of Cu (2.0 )and Mg (2.2 )atoms,which indicates aweak CuÀMg interaction.…”
Section: Organocopper(i) Compounds Are Ubiquitously Involved Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neutral N,N-chelated spiro copper complexes are relatively common, the anionic C,N- or C,C-cheated spiro counterparts are sporadic. As mentioned above, Xi’s group found that the C,C-bidentate ligand is an excellent platform to build up diversified coordination complexes across the periodic table [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The chelating effect increases the thermal stability of these organometallic species, facilitating isolation and following characterization.…”
Section: Mononuclear Organocopper Complexesmentioning
confidence: 99%
“…The remaining two higher order magnesiates, have a subtly different structure and can be described as 'magnesiacyclopentadienes'. 17 By reacting substituted 1,4dilithio-1,3-butadienes with 0.5 molar equivalents of MgCl2 in the presence of TMEDA, the spiro-dilithio magnesiacyclopentadiene complexes (TMEDA)2Li2Mg[CR 1 2(CR 2 2)2CR 1 2]2 9 and 10 (for 9, R 1 = SiMe3; R 2 = Me; and for 10, R 1 = SiMe3; R 2 = Ph) are formed ( Figure 7).…”
Section: Alkyl/aryl Lithium Magnesiate Complexesmentioning
confidence: 99%